Endothelial Dysfunction in Trauma: Pathogenesis, Clinical Significance, Diagnosis and Treatment - V. V. Matyukhin; S. S. Maskin; V. V. Aleksandrov; G. P. Dudchenko; O. V. Ostrovsky; M. N. Alimov; O. V. Werle (Неотложная медицинская помощь, 2025)
Severe trauma is a major medical and social problem. Severe injures is the leading cause of death in people under the age of 44. Many trauma survivors become disabled. Apart from immediate death of victims at the prehospital stage, in-hospital mortality is usually due to hemorrhagic shock, coagulopathy, systemic inflammation, both infectious and non-infectious nature, and multiple organ failure. In the last decade, a significant role of endothelial dysfunction in the development of these pathological processes has been recognized. Endothelial dysfunction refers to excessive activation of the endothelium, accompanied by multisystem manifestations. This literature review presents current data on the physiology of normal endothelium, the pathogenesis of endothelial dysfunction in trauma, its role in the development of systemic inflammation, increased vascular permeability and coagulopathy, and methods for its diagnosis and correction.